Justice and employee engagement: Examining the mediating role of trust in Indian B-schools. Issue 1 (7th April 2015) - Gupta, Manish; Kumar, Yln
Abstract : Purpose: – The purpose of this paper is to examine the mediating role of trust in the relationship of justice and employee engagement (EE) in Indian B-schools. Design/methodology/approach: – Multiple regression was carried out on the responses obtained from 320 academics working in different Indian B-schools. Findings: – The results showed that vertical trust (VT) partially mediates the procedural justice (PJ) and the EE relationship. Distributive justice, PJ, VT and EE were found to be significantly correlated with each other. Research limitations/implications: – A very important implication from the findings is that the research will help the Indian B-schools engage their employees in a better manner and face the challenging environment. Future research can be carried out on finding the mediating effects of leader member exchange on VT-EE relationships with other levels of higher education. Originality/value: – The current study empirically proved that a good level of PJ leads to a high level of VT and which ultimately results in engaged academics in Indian B-schools.